TRAÇOS FUNCIONAIS DE DUAS LEGUMINOSAS ARBÓREAS: TRANSLOCAÇÃO DE NUTRIENTES E ASSOCIAÇÃO MICORRÍZICA - Junior, Roberto Antonio da Costa Jeronimo (2020)
The environmental impacts caused by trees in reforestation projects can be influenced by the nutritional requirements of the species and the quality of the litter that contributes to the soil. Species that show faster growth tend to accumulate more nutrie